Secondhand smoke (SHS) exposure among children. Implications for a smoke free home educational programme - Precioso, José (2009)
Background: SecondHand Smoke (SHS) exposure among children represents a major cause of serious health problems. Children exposed to SHS are at an increased risk of serious health problems like sudden infant death syndrome, pneumonia, ear infections and more severe asthma. Studies have shown that SHS exposure is quite common, occurring frequently at home and in the car. A previous study conducted in Portugal (2002) with 1141 children with 12-15 years old revealed that 38% of them were daily or occasionally exposed to SHS due to the smoke of parents or siblings at home. No information was available for 9-10 years old. Objectives: 1) To determine parents smoking prevalence in the sample; 2) To determine the prevalence of parents smoking at home. Methods: An anonymous self-administered structured questionnaire was submitted to 793 students (aged media 9.14 years; 48.6% girls; 51.4% boys), enrolled in Portugal’s Northern Region’ schools. Results: 15.5% of the mothers and 37.0% of the fathers are daily smokers; 11.4% of the mothers and 25.8% of the fathers are daily or occasional home smokers. 14,2% of children report that at least one of the co-inhabitants (father, mother, brother/sister or other) smokes daily at home and 28.0% refer they smoke occasionally at home. Conclusions: Almost half of the children evaluated are daily or occasionally exposed to SHS, because a high proportion of parents or other people like brother/sister regularly smoke at home. Health professionals, especially Pediatricians, should systematically inquire and advise parents about the health risks of SHS and advise them to quit or even forward to a specialised query.